Feasibility of Spring Onion (Allium fistulosum L.) farming in the California Cialam Jaya Agrotourism Area, Tanea Village, Konda District, South Konawe Regency - Ramadani; Fyka, Samsul Alam; Yusriadin (International Journal of Technology and Education Research, 2025)
This study aims to determine the productivity, income, farm feasibility, and break-even point of scallion (Allium fistulosum L.) farming in the California Cialam Jaya Agrotourism Area, Tanea Village, Konda District, South Konawe Regency. The research method used was a survey method with a quantitative descriptive approach. The data used included primary and secondary data, collected through interviews and observations with farm managers. Data analysis used included analysis of productivity, income, farm feasibility using the R/C Ratio approach, as well as Break Even Point (BEP) analysis in terms of production, revenue, and selling price. The results of the study showed that the productivity of spring onion farming was 8,400 kg/ha, with an income of Rp22,224,167 per planting season and an R/C Ratio of 2.12, indicating that spring onion farming is financially viable. The break-even point for production was 471 kg/ha, the BEP for revenue was Rp2,807,000, and the BEP for selling price was Rp4,708.53, all indicating that actual production exceeded the break-even point, thus making this farming profitable. Based on these results, spring onion farming in the study area was declared feasible and has the potential for further development